2019
DOI: 10.3390/coatings9080490
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Boundary Layer Flow of a Viscoelastic Fluid Past a Nonlinear Stretching Sheet in the Presence of Viscous Dissipation Effect

Abstract: This paper numerically investigates the viscous dissipation effect on the boundary layer flow of an electrically-conducting viscoelastic fluid (Walter’s B liquid) past a nonlinear stretching sheet. The partial differential equations governing the flow problem are transformed into ordinary differential equations through similarity variables. The transformed equations are then solved using the Keller box method. A careful evaluation of the influence of the pertinent parameters on the velocity field and temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Mustapha 20 examined the analytical solution of viscoelastic fluid generated by a nonlinearly stretching sheet by employing the method of homotopy analysis. The impact of viscous dissipation on the viscoelastic fluid flow caused by a vertical nonlinear stretching sheet was quantitatively examined by Jafar et al 21 while Seth et al 22 investigated the influence of velocity slip on the Dufour and Soret phenomena of MHD viscoelastic fluid created by a nonlinearly stretched surface. It was found that the viscoelasticity parameter reduces the fluid’s temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mustapha 20 examined the analytical solution of viscoelastic fluid generated by a nonlinearly stretching sheet by employing the method of homotopy analysis. The impact of viscous dissipation on the viscoelastic fluid flow caused by a vertical nonlinear stretching sheet was quantitatively examined by Jafar et al 21 while Seth et al 22 investigated the influence of velocity slip on the Dufour and Soret phenomena of MHD viscoelastic fluid created by a nonlinearly stretched surface. It was found that the viscoelasticity parameter reduces the fluid’s temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the fluid, is also considered as a nonlinear function of the distance from the slit, where is a positive constant and is the ambient temperature of the fluid. Thus, using the conventional boundary layer approximation, the viscoelastic fluid equations governing the momentum and energy equations may be expressed as follows 11 , 21 . where and are the fluid flow's velocity components along and directions, , , , , , , , and are respectively, the viscosity, kinematic viscosity, material constant, fluid density, electrical conductivity, gravitational acceleration, thermal expansion coefficient, heat capacitance, radiative heat flux, and thermal conductivity of the fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of entropy generation on a moving viscoelastic nanofluid over a stretched surface [29] and the dissipation of viscoelastic fluid on non-linear surface [30] have been investigated. Other interesting results were made by Gholinia et al [31] and Ogunseye et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…They have considered the local nonsimilarity method and OHAM to solve the resulting equation. Jafar et al [14] studied the MHD boundary layer flow of a viscoelastic fluid past a nonlinearly stretching sheet in the presence of a viscous dissipation effect.…”
Section: Introductionmentioning
confidence: 99%